Contextual Analysis of the Site - Gorbova, O. V.; Bohutskyi, D. V. (Science and Transport Progress, 2024)
Purpose. The purpose of this article is to describe the method of contextual website research, which is an alternative to traditional benchmark tests. Unlike laboratory tests, where conditions are strictly controlled, contextual research allows you to evaluate the usability of a website in a real context, taking into account the factors that affect the user in his or her usual environment. This means that researchers observe users interacting with a website in their natural environment, such as at home or at work, which allows them to gain a more relevant understanding of the user experience. Methodology. We used the contextual research method, which involves detailed observation and interviewing a small group of users about certain aspects of a website. This helps to get a realistic picture of how the user perceives and uses the site in real conditions, in the context of websites. Researchers can observe how users use the website, what tasks they are trying to accomplish, what difficulties they encounter, and how they interact with other tools and programs. Findings. The study makes it possible to greatly simplify the evaluation of website usability using certain approaches and developed software. Using contextual research, it is possible to identify shortcomings that would not be noticeable during laboratory tests and suggest improvements that increase the usability of a website. Originality. The study is based on key principles such as contextualization, collaborative evaluation, usability as the main indicator, and focus on the subject matter. This allows us to gain a deeper understanding of how users interact with a website in real life, not just in an artificially created laboratory environment. Practical value. The results of the work allow us to use the method of contextual research in a wide range of human activities within websites of different orientations to improve the user experience. This can be especially useful for websites that are developed for certain groups of users, such as people with disabilities or the elderly.